International review of national‐level guidelines on end‐of‐life care with focus on the withholding and withdrawing of artificial nutrition and hydration. Issue 9 (6th August 2019) - Mayers, Thomas; Kashiwagi, Shiho; Mathis, Bryan J.; Kawabe, Makiko; Gallagher, Joshua; Morales Aliaga, Maria L.; Kai, Ichiro; Tamiya, Nanako
Abstract : Aim: The purpose of the present study was to collate examples of end‐of‐life care guidelines from various counties, examine their contents, and gain an overall picture of how end‐of‐life care guidance is offered to physicians and care providers internationally. Methods: In this study, eight researchers worked independently to source and examine national‐level end‐of‐life care guidelines from different countries and regions. Data collected by each researcher were gathered into a unified table. The items in the table included basic information (publisher, year, URL etc.) and more specific items, such as the presence/absence of legal information and family's role in decision‐making. These data were then used to identify trends, and examine the mechanics and delivery of guidance on this topic. Results: A total of 54 guidelines were included in the study. All the guidelines were published between 2000 and 2016, and 60% ( n = 33) were published after 2012. The length of the guidelines varied from two to 487 pages (median 38 pages), and had different target audiences – both lay and professional. A total of 38 (70%) of the guidelines included information about the relevant laws and legal issues, 47 (87%) offered advice on withholding and withdrawing treatment, 46 (85%) discussed the family's role in decision‐making and 46 (85%) emphasized the teamwork aspect of care. Conclusions: The present findings show that end‐of‐life care guidelines are generally made reactively in response to the trend toward patient‐centered care, and that to create effective guidelines and implement them requires multilevel cooperation between governmental bodies, healthcare teams, and patients and their families.Geriatr Gerontol Int 2019; 19: 847–853 .